To solve the surds given, we shall begin by taking the common factors in either side of the equation, as shown below;
![\begin{gathered} \sqrt[]{8x-42}=\sqrt[]{21x+49} \\ =\sqrt[]{8x-42}=\sqrt[]{49((3)/(7)x+1)} \\ =\sqrt[]{8x-42}=\sqrt[]{49}*\sqrt[]{(3)/(7)x+1} \\ \sqrt[]{8x-42}=7\sqrt[]{(3)/(7)x+1} \\ \text{Cross multiply and you'll have} \\ \frac{\sqrt[]{8x-42}}{\sqrt[]{(3)/(7)x+1}}=7 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/v47y62wfsz6j08fpyzkdicygr5tqrtm0qp.png)
Note that there is no common factor for both radical expressions as shown in the steps above. Therefore, there is no solution for this equation.